The Profession of IT: Can Generative AI Bots Be Trusted? - Denning, Peter J. (Communications of the ACM, 2023)
This article examines the use of generative artificial intelligence (AI), namely OpenAI’s ChatGPT, with an emphasis on trust as well as its impact on education and jobs. The author discusses limitations to ChatGPT and how these can lead to errors in its responses but also highlights ways chatbots can be used to assist in a professional’s work.